The effect of internal control systems and whistleblowing systems on fraud prevention with bugis cultural values as moderation variables - Rahayu Wiliana; Syamsuddin; Nadhirah Nagu (International Journal of Multidisciplinary Research and Studies, 2023)
The purpose of this study was to analyze the effect of (1) the internal control system on fraud prevention, (2) the whistleblowing system on fraud prevention, (3) Bugis cultural values in moderating the internal control system on fraud prevention, (4) Bugis cultural values in moderating whistleblowing. a system against fraud prevention. This research was conducted at 13 SKPD in Sidenreng Rappang Regency with a research period of two months, starting from January to February 2023. This research used a quantitative research method. The sampling procedure in this study was based on a nonprobability sampling design by adopting purposive sampling, with the population in this study totaling 172 respondents. This study used primary data, the data collection method was carried out by distributing questionnaires with a self-administered method. The statistical method used to test the hypothesis is to use the Structural Equaton Model (SEM), and the test is carried out using Smart-PLS 3.0. The results of the study show that the internal control system has a positive effect on fraud prevention, and the whistleblowing system has a positive effect on fraud prevention. Whereas in the moderation effect in this study, Bugis cultural values strengthen the influence of the internal control system on fraud prevention, and Bugis cultural values do not moderate the effect of the whistleblowing system on fraud prevention.